PERENCANAAN EMBUNG TAMBAKROMO UNTUK MEMENUHI KEBUTUHAN AIR BAKU - Fahmi, Mushafa; Halim, Fandy; Atmojo, Pranoto Samto; Sriyana, Sriyana (Jurnal Karya Teknik Sipil, 2013)
The increasing scarcity of water resources, there needs to be an effort that must be implemented to meet the needs of the water. One way PT. Indocement to meet the water requirement of 60 liters / second to harness the potential of Beku river with Tambakromo Embung development plan, in Wukirsari Village, District Tambakromo, Pati. Based on the mainstay discharge analysis by the method of FJ mock obtained the discharge of 120 liters / sec. For the body design of the small dam used the flood discharge hydrological data with HSS Gamma I method with flood discharge plan 1000 years return period amounted 116.92 m3/second. Tambakromo Small Dam capacity is 5,000,000 m3. Tambakromo Small Dam height is 20 meters, 7 meters wide summit reservoir, spillway width of 15 meters, spillway height is 2 meters. Estimated cost to build Tambakromo Small Dam amounted Rp.33.874.000.000, 00.